2020
DOI: 10.2147/opth.s254705
|View full text |Cite
|
Sign up to set email alerts
|

<p>Difluprednate 0.05% versus Prednisolone Acetate Post-Phacoemulsification for Inflammation and Pain: An Efficacy and Safety Clinical Trial</p>

Abstract: Background: The purpose of this study was to compare the efficacy and safety of difluprednate 0.05% (PRO-145) versus prednisolone acetate 1% (Prednefrin ® SF), for management of postoperative inflammation and pain, after cataract surgery. Methods: This was a Phase III, multicenter, prospective, double-blind, clinical trial. Intentto-treat population included 178 post-phacoemulsification patients that were assigned to receive either PRO-145, or prednisolone. One day after unilateral eye surgery, patients instil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 21 publications
0
5
1
Order By: Relevance
“…No significant differences in the analysis of AC cells and flare were observed between the two drug groups at any time of follow-up in a multicenter RCT studied in Mexico [ 21 ]. Khalaf Allah et al, in their systematic review, have reported that after small incision cataract surgery, difluprednate was superior in clearing AC cells at one week (OR=2.5, p>0.00001) and at two weeks (OR=2.5, p=0.04), as well as clearing the AC flare at two weeks (OR=6.7, p=0.04).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…No significant differences in the analysis of AC cells and flare were observed between the two drug groups at any time of follow-up in a multicenter RCT studied in Mexico [ 21 ]. Khalaf Allah et al, in their systematic review, have reported that after small incision cataract surgery, difluprednate was superior in clearing AC cells at one week (OR=2.5, p>0.00001) and at two weeks (OR=2.5, p=0.04), as well as clearing the AC flare at two weeks (OR=6.7, p=0.04).…”
Section: Discussionmentioning
confidence: 99%
“…However, if this persists for a long time, it causes intraretinal cystic spaces, otherwise called subclinical cystoid macular oedema (SCME) [ 19 , 20 ]. The postsurgical inflammation in the macula following topical steroid administration has not been studied adequately using OCT [ 19 - 21 ]. Few studies on spectral-domain OCT documented the resolution of pseudophakic CME after administration of topical difluprednate [ 19 - 21 ].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations